PERSEPSI GENERASI Z TERHADAP PENGARUH MEDIA SOSIAL PADA MOTIVASI BELAJAR FISIKA SISWA SMA - Dinda; Sutrisnawati Mehora (STKIP Subang, 2026)
This study aims to analyze Generation Z students' perceptions of the influence of social media on their motivation to learn physics at the high school level. Social media has become an integral part of students' daily lives, providing both positive and negative impacts on the learning process. This study used a quantitative descriptive method with a questionnaire distributed to high school students. Data were analyzed to identify student perceptions and the relationship between social media use and their motivation to learn physics. The results showed that some students perceived positive benefits in the form of easy access to additional materials and educational content, but the majority of students were more distracted by social media, resulting in decreased focus, concentration, and motivation to learn physics. In general, negative perceptions of the influence of social media were more dominant than positive perceptionsKeywords: Generation Z, social media, learning motivation, physics education